Transition Economies During Global Economic Crisis: A Difference in Differences Approach - Filipović, Sanja; Miljković, Marko (Industrija, 2014)
This paper describes how the global economic crisis impacted economies in transition, which in terms of GDP decline, were the most negatively impacted economies in the world. Therefore the region went from a growth rate of around 8.4% in 2007 to -3.9% in 2009. The aim of this paper is to determine which countries depending on the level of progress in the transitional reforms implementation (measured by transition indicator) were more exposed to the effects of the global economic crisis, i.e. which countries in the five-year period 2009-2013 faster showed progress as measured by the economic growth rate. The research is based on difference in differences (DinD) methodology and covered 29 economies in transition. The results showed that economies with lower progress in the way of transition reforms (transition indicator is less than 3) suffered smaller impact of the crisis in its first wave in 2009. In addition, this subset of countries in transition better overcame the crisis in the five-year period 2009-2013 given that they showed 18 percentage points higher cumulative rate of growth in those five years than the transition countries that adopted all the principles of market economy.